The legacy of Nazi occupation : patriotic memory and national recovery in Western Europe, 1945-1965 - Lagrou, Pieter (Cambridge ; New York : Cambridge University Press, 1999)
This book analyses how France, Belgium and the Netherlands emerged from the Second World War. Pieter Lagrou offers a genuinely comparative approach, based on extensive archival research. Brilliantly researched and fluently written, this book will be of central interest to all scholars and students of twentieth-century European history.
Appropriating victory and re-establishing the state -- Heroes of a nation : Belgium and France -- A nation of heroes : the Netherlands -- Displaced populations -- The challenge to the post-war state : Belgium and the Netherlands -- Pétain's exiles and De Gaulle's deportees -- Labour and total war -- Moral panic : "the soap, the suit and above all the Bible" -- Patriotic scrutiny -- "Deportation" : the defence of the labour conscripts -- Plural persecutions -- National martyrdom -- Patriotic memories and the genocide -- Remembering the war and legitimising the post-war international order.
Includes bibliographical references (pages 307-322) and index.
Print version record.
eBooks on EBSCOhost
Keywords: Reconstruction (1939-1951) -- Europe; Europe -- History -- 1945-; Memory; Reconstruction, 1939-1951 -- Europe; Europe -- Histoire -- 1945-; HISTORY; Reconstruction (1939-1951); Memory; Europe; Bezettingen; Collectief geheugen; Herstel; Tweede Wereldoorlog; Politieke geschiedenis; Europa (geografie); Since 1945; Electronic books; History